2016
DOI: 10.7860/jcdr/2016/16852.7249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CT and MRI Findings among Patients Presented with Chief Complaint of Headache in Central India

Abstract: CT/MRI in patients without red flag or CWC sign yields very low percentage of clinically significant positive findings in neuroimaging. In the absence of these, the only reason for CT or MRI scan seems to reassure the patients and their loved ones. CT or MRI as a screening tool in these patients has limited value in term of cost effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…65 Furthermore, the utility of other red flags in predicting secondary etiologies of headache has not been well studied in HIV-uninfected populations and not studied at all in HIVþ populations. [66][67][68][69] The few studies that have been conducted indicate that abnormal findings on neurologic examination are the strongest predictor of intracranial pathology, 68,69 but this, too, poses challenges in low-income countries. Neurologists are scarce, and frontline health care providers with minimal training in neurology may not be able, or have the equipment, to reliably detect subtle abnormalities such as a visual field deficit, or even critical signs such as papilledema.…”
Section: Secondary Headachesmentioning
confidence: 99%
“…65 Furthermore, the utility of other red flags in predicting secondary etiologies of headache has not been well studied in HIV-uninfected populations and not studied at all in HIVþ populations. [66][67][68][69] The few studies that have been conducted indicate that abnormal findings on neurologic examination are the strongest predictor of intracranial pathology, 68,69 but this, too, poses challenges in low-income countries. Neurologists are scarce, and frontline health care providers with minimal training in neurology may not be able, or have the equipment, to reliably detect subtle abnormalities such as a visual field deficit, or even critical signs such as papilledema.…”
Section: Secondary Headachesmentioning
confidence: 99%
“…A study done in India by Garjesh Singh Rai et al (2016) found that headache is more common in female (62.6%) than male (37.4%) and the commonest age group ranging from 20-30 years (29%) followed by 30-40 years (27.8%) and 40-50 years (15.8%). 16 Another study done in the United States of America showed that migraine headache, the commonest primary headache diagnosed in primary healthcare setting peaks between the ages of 25-55 years.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in India by Garjesh Singh Rai et al (2016) found that headache is more common in female (62.6%) than male (37.4%) and the commonest age group ranging from 20-30 years (29%) followed by 30-40 years (27.8%) and 40-50 years (15.8%). 16 Another study done in the United States of America showed that migraine headache, the commonest primary headache diagnosed in primary healthcare setting peaks between the ages of 25-55 years. 17 In our study, female patients (50.96%) were slightly more than the male (49.04%) patients and majority of the participants were in the age group of >20 to ≤40 years (54.14%) followed by >40 to ≤60 years (25.47%).…”
Section: Discussionmentioning
confidence: 99%
“…The major integrant of paranasal sinus includes the mucus secretions, the hair-like structure that drains the mucus out of the paranasal sinus, and the sinus ostium. Any inflammation in above-mentioned components render the sinus liable to infections [2].…”
Section: Introductionmentioning
confidence: 99%